Kadar Lemak, Protein Dan Sifat Sensoris Kornet dengan Substitusi Jantung Pisang - Nala Naeli Nur Fauziyah; Joko Teguh Isworo; Yunan Kholifatuddin Sya'di (Universitas Muhammadiyah Semarang, 2017)
Banana blossom is a food rich in nutrients. During this time the benefits of banana blossomis limited to vegetable product such as jerky and